Tinjauan Hukum Kenaikan Pajak 12% atas Barang Mewah melalui PPnBM - Dina Gita Prianti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The increase in the PPnBM rate to 12% in Law 7/2021 on Luxury Goods is a fiscal reform strategy to increase state revenue and control the consumption of luxury goods. This policy aims to broaden the tax base and reduce socio-economic inequality. From a legal perspective, its implementation must uphold the principles of justice, legal certainty, and protection of taxpayer rights. Clear derivative regulations, transparent implementation, and strict supervision are needed to prevent abuse. This paper analyzes the policy through normative and conceptual approaches of tax administration law and fiscal economics.